THE EFFECT OF DISTRIBUTION COSTS, OPERATING COSTS, AND PRODUCTION COSTS ON COMPANY PROFITS WITH THE INTERVENING VARIABLE SALES VOLUME - Eko Budi Satoto (Jurnal Apresiasi Ekonomi, 2026)
This study aims to quantify the impact of distribution, operational, and production cost categories on sales volume and subsequent corporate earnings. Employing structural equation modeling (SEM) via Smart PLS version 3.0, the analysis establishes several statistically significant positive partial relationships. Specifically, each cost type including distribution, operations, and production positively influences both company profits and sales volume. Moreover, sales volume exerts a positive partial effect on profits. Of particular importance, sales volume emerges as a significant partial mediator in the pathways linking distribution costs, operating costs, and production costs to corporate profitability. The novelty in research is sales volume as an intervening variable. The results of this study can contribute ideas and information that can be used as input for companies related to cost and revenue planning in achieving company goals, namely maximizing profits. As well as the company’s ability to determine production costs will affect the level of profit earned and the results of this study can be taken into consideration in carrying out promotional activities and distribution channels to increase sales and company profits. Researchers only took 3 independent variables, namely Distribution Costs, Operating Costs, and Production Costs. This research period is only from 2021-2025. Keywords: Distribution Costs, Operating Costs, Production Costs, Sales Volume, Company Profit